2016
DOI: 10.3390/ijerph13050512
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Awareness, Treatment and Control of Diabetes Mellitus—A Population Based Study in Shanghai, China

Abstract: In this study, we aimed to investigate the prevalence, awareness, treatment, and control of diabetes in Shanghai, China. A sample of 3600 residents aged from 18 to 80 years selected by a randomized stratified multiple-stage sampling method in Shanghai was investigated, with blood samples collected. Diabetes was defined as fasting plasma glucose (FPG) ≥ 7.0 mmol/L, or glycated haemoglobin (HbA1c) ≥ 6.5% (48 mmol/mol), or previous diagnosis by a physician. Adequate control of diabetes was taken as a level of HbA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 21 publications
2
18
2
Order By: Relevance
“…Among the diabetes patients who use the healthcare cloud information platform for self‐management, the control rate of diabetes was maintained at 63% to 72%. The control rate in recent years was also higher than that at the initial use of the model, and much higher than the rate of 48.06% before the model was used. This control rate is higher than in low‐income countries, such as India (39.6%), and close to that in high‐income countries, such as Portugal (63.2%) .…”
Section: Discussionmentioning
confidence: 70%
“…Among the diabetes patients who use the healthcare cloud information platform for self‐management, the control rate of diabetes was maintained at 63% to 72%. The control rate in recent years was also higher than that at the initial use of the model, and much higher than the rate of 48.06% before the model was used. This control rate is higher than in low‐income countries, such as India (39.6%), and close to that in high‐income countries, such as Portugal (63.2%) .…”
Section: Discussionmentioning
confidence: 70%
“…Studies have demonstrated poor control of cardiovascular risk factors and low adherence to stroke secondary prevention efforts in China (Gao et al, 2013;Lu et al, 2017;Pan et al, 2016;Peng et al, 2014;Qin et al, 2016). Even for patients with a history of cardiovascular surgeries, therapy compliance was still unimproved (Halle et al, 2018).We assume that they may be unaware of, and underestimate the importance of, controlling risk factors to reduce stroke incidence (O'Donnell et al, 2016;Soroush et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, we should note that in clinical practice in China, only 21.5%-25% of stroke patients arrived at hospital within 3 hr, and the overall rate of using an ambulance was 15.4%-23.1% (Jiang TA B L E 3 Stroke recognition rate (SRR) and correct action rate (CAR) in individuals with and without CVD among the surgery group intervention, patients were still at a high risk for stroke due to their markedly high risk factors and poor control of hypertension, diabetes, and dyslipidemia (Lu et al, 2017;Pan et al, 2016;Qin et al, 2016). Nearly three-fourths of patients stated that they would call an ambulance for stroke onset in the questionnaire survey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no national registration system of DM in China, and the awareness rate of diabetes is extremely lower in China than that in western countries (Li et al, 2013;Qin et al, 2016). Thus, the self-reported disease duration in Chinese diabetic patients might be inaccurate, which cannot be an useful predictor for distinguishing DN from NDRD.…”
Section: Discussionmentioning
confidence: 99%